Metonymy in Motion: How Metonymy Shapes Soccer Narratives and Enhances ELT Practices - Juliana, Juliana; Mulyadi , Mulyadi (Universitas Lancang Kuning, 2025)
This study addresses a critical gap in sports linguistics by exploring the cognitive semantic role of metonymy in digital soccer journalism, an area that remains underexamined despite its pervasive use in media discourse. Using a corpus-based cognitive semantic approach, this qualitative study examines the prevalence and patterns of metonymy in soccer news articles published on Goal.com. A purposive sampling technique was employed to select 250 news articles collected from August 2021 to May 2024, providing a robust dataset for analysis. The findings reveal that